Teaching tourism students with cultural intelligence - Moira Kostic Bobanovic; Jasmina Grzinic (UTMS Journal of Economics, 2019)
There is need to advance cross-cultural educations to better prepare tourism students for the nuances of a modern, multicultural century. This article makes a contribution by proposing an approach to developing students' cultural intelligence that is based on the cultural intelligence (CQ) model and experiential learning theory. The Cultural intelligence index was obtained through the Cultural Intelligence Scale (Ang et al., 2007). This longitudinal research was done by measuring CQ of students who attend cross-cultural tourism and foreign languages course at the beginning of the first year and at the end of the year. Cultural knowledge is incorporated into our classroom teaching styles and methodology. The study involved 143 students from Juraj Dobrila University in Pula studying tourism. The implementations of methods in teaching cross culture result in the improvement of students' CQ and all of its components (metacognition, cognition, motivation and behaviour). We discuss our findings in relation to cultural adjustments and development of culturally intelligent students who will become multiculturally educated and globally engaged citizens.
Keywords: A22; M21; 330; tourism; trends; multiculturality; cultural exchange; education